1977
DOI: 10.1007/bf00222778
|View full text |Cite
|
Sign up to set email alerts
|

O�genesis in a marine teleost, Blennius pholis L.

Abstract: Oögenesis in the oviparous marine teleost, Blennius pholis L., is examined. Eleven developmental stages are identified by ultrastructural observations when changes in the distributions of the organelles and inclusions are described. An exogenous source for the protein yolk precursors is indicated, but less clear is the endogenous contribution. Changes in the follicle epithelium are described together with the formation of the zona which is considered to be follicular in origin. Two types of follicle cell are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
3

Year Published

1980
1980
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
4
28
0
3
Order By: Relevance
“…Several staging systems for oocyte development have been proposed, which incorporate physiological, biochemical, morphological and histological criteria, including follicle size, somatic tissue types and yolk presence (Yamamoto, 1957;Kuo et al, 1974;Shackley and King, 1977;Nagahama, 1983Nagahama, , 1994Selman et al, 1986Selman et al, , 1993Bromage and Cumaranattmga, 1988). The major developmental events that occur, however, can broadly be classified into six phases or periods according to the state of oocyte growth: oogenesis, primary oocyte growth, cortical alveolus stage, vitellogenesis, maturation, and ovulation (Bromage and Cumaranatunga, 1988).…”
Section: Oocyte Growthmentioning
confidence: 99%
“…Several staging systems for oocyte development have been proposed, which incorporate physiological, biochemical, morphological and histological criteria, including follicle size, somatic tissue types and yolk presence (Yamamoto, 1957;Kuo et al, 1974;Shackley and King, 1977;Nagahama, 1983Nagahama, , 1994Selman et al, 1986Selman et al, , 1993Bromage and Cumaranattmga, 1988). The major developmental events that occur, however, can broadly be classified into six phases or periods according to the state of oocyte growth: oogenesis, primary oocyte growth, cortical alveolus stage, vitellogenesis, maturation, and ovulation (Bromage and Cumaranatunga, 1988).…”
Section: Oocyte Growthmentioning
confidence: 99%
“…Detailed histological studies of oogenesis have been performed on only a few species. What is known of goby ovaries agrees with the general oviparous teleost patterns (Rajalakshmi, 1966; Shackley & King, 1977; Brummett et al ., 1982; Selman & Wallace, 1986; Selman et al ., 1991; Grier, 2000). The oocytes of gobies are unusual in that they are ellipsoid and adhesive rather than spherical, with a tuft of attachment filaments present around the oocyte micropyle.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of cortical alveoli, those containing filamentous material and those containing latticed material, were observed in oocytes from Japanese eel. The structure of cortical alveoli has been the subject of discussion in several papers; thus, in killifish Fundulus heteroclitus , cortical alveoli only contained flocculent material, 14 whereas two different types of cortical alveoli were observed in the oviparous marine teleost Blennius pholis 15 . In the present study, all cortical alveoli observed at the migratory nucleus stage were those possessing only latticed contents, although two types were observed during earlier stages of oogenesis.…”
Section: Discussionmentioning
confidence: 40%
“…In the killifish, the filamentous structure in the cortical alveoli appears to be organized in a hexagonal pattern as the oocyte approaches maturity 14 . Shackley and King suggested that the structural changes of the proteins stored in the cortical alveoli may be due to the uptake of water into the oocytes in this species 15 . Similarly, the gradual loss of filamentous proteins in the cortical alveoli, which are observed during eel oocyte development, may be related to hydration, just prior to ovulation and fertilization in the Japanese eel.…”
Section: Discussionmentioning
confidence: 99%